Tin compounds containing tin-oxygen double bond, and photoresist composition containing the same

Tin compounds with a tin-oxygen double bond and organic ligands are used in photoresist compositions to address issues of line edge roughness and environmental reactivity, resulting in high-quality, ultrafine patterns with improved reproducibility and resistance to external factors.

JP2025051654AActive Publication Date: 2025-04-04IND FOUND OF CHONNAM NAT UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024162055
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2024-09-11
Filing Date
2024-09-19
Publication Date
2025-04-04
Estimated Expiration
2044-09-19

AI Technical Summary

Technical Problem

Conventional photoresists face challenges such as line edge roughness (LER) and patterning inhomogeneity due to chemical stochastic effects, and they react with moisture and carbon dioxide, affecting pattern reproducibility.

Method used

Development of tin compounds with a central backbone containing a tin-oxygen double bond and an organic ligand, which exhibit excellent photosensitiveness and corrosion resistance, and are used in a photoresist composition to form high-quality patterns without reacting with gas molecules.

Benefits of technology

The tin compound-based photoresist composition achieves excellent photosensitiveness, corrosion resistance, and high-quality pattern formation with thin thickness even in ultrafine patterns, while preventing pattern degradation due to external environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025051654000001_ABST
    Figure 2025051654000001_ABST
Patent Text Reader

Abstract

To provide a tin compound including a tin-oxygen double bond, a photoresist composition including the same, and a method for forming a photoresist pattern using the same.SOLUTION: There is provided a method for forming a photoresist pattern that includes the step of dissociating an organic ligand of an organometallic compound upon light exposure to cause an addition reaction between metal molecules.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to tin compounds containing tin-oxygen double bonds, photoresist compositions containing same, and methods of forming photoresist patterns using same. [Background technology]

[0002] Research continues into the miniaturization of semiconductor patterns, which is essential for manufacturing highly integrated semiconductor devices. Semiconductor miniaturization reached its limit in the early 2000s. In the early days, miniaturization was achieved through lithography processes using light sources with short wavelengths, but after the 90nm technology node, innovative technologies were introduced to maintain high performance and low power consumption in addition to simple miniaturization. The development of lithography technologies such as ArF immersion technology and double patterning allowed miniaturization to be maintained without changes in light source, but this caused problems such as process complexity and increased costs. In 2020, EUV lithography technology was introduced for mass production of 7nm-class semiconductors, and related research is being actively conducted.

[0003] Photolithography is the step in semiconductor manufacturing that creates circuits by using light to transfer designs made on a mask onto the surface of a wafer. When exposed to ultraviolet (UV), extreme ultraviolet (EUV) and electron beam radiation, photoresist undergoes a chemical change that creates a pattern. In positive resist, the exposed areas are selectively removed, while in negative resist, the unexposed areas are removed.

[0004] Photoresists are divided into chemically amplified (CAR) and non-chemically amplified types. CAR contains a photoacid generator that generates acid by light, so that the reaction can be amplified even with a small amount of light. However, CAR can cause line edge roughness (LER) problems and non-uniformity in pattern formation due to the stochastic effect. Chemical stochastic effect means randomness that occurs during the reaction process of chemicals in the photoresist, which is influenced by various factors such as reactivity, molecular movement, and reaction mechanism. Photonstochastics is randomness that occurs from the number and distribution of photons irradiated to the photoresist, and the range of fluctuation can be large especially in low light exposure.

[0005] To solve these problems, inorganic photoresists are being researched. Inorganic photoresists have excellent corrosion resistance and mechanical strength, and can be stably formed even in ultra-fine patterns, and can maintain high sensitivity due to their high EUV absorption rate. In particular, photoresists containing inorganic elements such as tin (Sn), indium (In), and hafnium (Hf) boast better EUV sensitivity and corrosion resistance than conventional organic photoresists.

[0006] Recent studies have shown that tin oxide clusters exhibit high EUV absorption and excellent line edge roughness (LER) characteristics, but additional research is still needed to improve EUV sensitivity. The development of such inorganic photoresists is considered to be a significant technological advancement that overcomes the limitations of conventional organic resists, provides resolution and sensitivity for the formation of ultra-fine patterns, and solves the problem of pattern collapse. [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Korean Patent Publication KR10-2024-0103989 A (2024.07.04) [Patent Document 2] Korean Patent Publication 10-2024-0104028 A (2024.07.04) Summary of the Invention [Problem to be solved by the invention]

[0008] An object of the present disclosure is to provide novel tin compounds containing tin-oxygen double bonds that have excellent photosensitivity and corrosion resistance.

[0009] One object of the present disclosure is to provide a photoresist composition comprising said tin compound.

[0010] Another object of the present disclosure is to provide a method for forming a photoresist pattern that can prevent deterioration in reproducibility of the photoresist pattern due to the external environment.

[0011] It is still another object of the present disclosure to provide a method for forming a photoresist pattern, which is capable of forming a high-quality photoresist pattern without reacting with gas molecules. [Means for solving the problem]

[0012] The present disclosure provides tin compounds that include a central skeleton containing a tin-oxygen double bond and organic ligands bonded to the central skeleton, which can be usefully used as photoresist materials.

[0013] In one embodiment, the central skeleton may be tin dioxide (O=Sn=O) or tin monoxide (O=Sn), and the organic ligand may be any one or more selected from the group consisting of formic acid, C1-C10 alkyl carboxylate, C2-C10 alkenyl carboxylate, C3-C10 cycloalkyl carboxylate, C6-C20 aryl carboxylate, halo C1-C10 alkyl carboxylate, C1-C10 alkylcarbonyloxy, C2-C10 alkenylcarbonyloxy, C3-C10 cycloalkylcarbonyloxy, C6-C20 arylcarbonyloxy, halo C1-C10 alkylcarbonyloxy, C1-C10 alkylcarbonylamine, and halo C1-C10 alkylcarbonylamine.

[0014] In one embodiment, the tin compound may be represented by the following chemical formulas 1 to 4. [Chemical formula 1] JPEG2025051654000002.jpg37170 [Chemical formula 2] JPEG2025051654000003.jpg37170 [Chemical formula 3] JPEG2025051654000004.jpg23170 [Chemical formula 4] JPEG2025051654000005.jpg14170 (In the above chemical formulas 1 to 4, R1 to R7 are each independently hydrogen, C1-C10 alkyl, or haloC1-C10 alkyl.)

[0015] Specifically, R1 to R4 may be, independently of one another, C1-C5 alkyl or haloC1-C5 alkyl, and R5 to R7 may be, independently of one another, hydrogen, C1-C5 alkyl or haloC1-C5 alkyl.

[0016] The present disclosure also provides a photoresist composition comprising the above-described tin compound.

[0017] The photoresist composition is an inorganic resist for extreme ultraviolet (EUV) and / or electron beam lithography, and upon irradiation with extreme ultraviolet (EUV) or an electron beam, chemical contrast is expressed by an additive reaction between inorganic components, and a pattern may be formed by an optional development process.

[0018] In particular, the photoresist may be an extreme ultraviolet (EUV) photoresist.

[0019] The present disclosure also provides a method for forming a photoresist pattern, comprising the step of dissociating an organic ligand of an organometallic compound upon exposure to light and carrying out an addition reaction between metal molecules.

[0020] In one embodiment, the method for forming a photoresist pattern may include the steps of: (a) applying a photoresist composition containing an organometallic compound to a substrate to form a thin film; (b) exposing the thin film to light; and (c) developing the exposed thin film using a developing solution.

[0021] In one embodiment, the organometallic compound may include a central skeleton containing a tin-oxygen double bond and organic ligands bonded to the central skeleton.

[0022] In one embodiment, the central skeleton may be tin dioxide (O=Sn=O) or tin monoxide (O=Sn).

[0023] In one embodiment, the exposure in step (b) may be performed by any one selected from an electron beam (E-beam), extreme ultraviolet (EUV), I-line, a krypton fluoride (KrF) laser, an argon fluoride (ArF) laser, deep ultraviolet (DUV), vacuum ultraviolet (VUV), X-ray, and an ion beam. Effect of the Invention

[0024] The photoresist composition including the tin compound according to one embodiment has excellent photosensitivity and corrosion resistance, and a photoresist pattern using the same can be formed with a thin thickness even in an ultrafine pattern.

[0025] The tin compound according to one embodiment is chemically stable and highly soluble in organic solvents, and can be usefully used as a photoresist material in a photoresist composition.

[0026] In addition, the photoresist composition including the tin compound according to one embodiment can prevent a problem in which pattern reproducibility is reduced due to external environments such as moisture and carbon dioxide when forming a photoresist pattern.

[0027] Furthermore, a photoresist composition containing a tin compound according to one embodiment can form a high-quality photoresist pattern under a low exposure dose without reacting with gas molecules, and is therefore industrially very useful. [Brief description of the drawings]

[0028] [Figure 1] FIG. 2 is a schematic diagram showing the mechanism of a method for forming a photoresist pattern according to an embodiment of the present disclosure. [Diagram 2] FIG. 2 is a schematic diagram showing the mechanism of a method for forming a photoresist pattern according to an embodiment of the present disclosure. [Diagram 3] 1 shows the results of analysis of tin compound 1 obtained in Example 1 using a Malditokh mass spectrometer (MALDI-TOF MS). [Figure 4] This is the result of estimating the molecular formula of the peak corresponding to (a) in Figure 3 by isotope distribution simulation calculation. [Diagram 5] This is the result of estimating the molecular formula of the peak corresponding to (b) in Figure 3 by isotope distribution simulation calculation. [Figure 6] 1 shows the results of photoelectron spectroscopy (XPS) analysis of tin compound 1 obtained in Example 1. [Figure 7]1 shows the results of FD-MS analysis of tin compound 2 obtained in Example 2. [Figure 8] This is the result of estimating the molecular formula of the peak corresponding to (b) in Figure 7 by isotope distribution simulation calculation. [Figure 9] 1 shows the results of FT-IR spectroscopy of tin compound 2 obtained in Example 2. [Figure 10] 1 shows the results of analysis of tin compounds 3-1 and 3-2 obtained in Example 3 using a Mol-Dietof mass spectrometer (MALDI-TOF MS). [Figure 11] This is the result of estimating the molecular formula of the peak corresponding to (a) in Figure 10 by isotope distribution simulation calculation. [Figure 12] This is the result of estimating the molecular formula of the peak corresponding to (b) in Figure 10 by isotope distribution simulation calculation. [Figure 13] 13 shows the results of observing a pattern irradiated with an exposure dose of 130 mJ / cm 2 in Example 9 using a CD-SEM. [Figure 14] 13 shows the results of observing a pattern irradiated with an exposure dose of 120 mJ / cm2 in Example 9 using a CD-SEM. [Figure 15] 13 shows the results of observing a pattern irradiated with an exposure dose of 110 mJ / cm 2 in Example 9 using a CD-SEM. [Figure 16] 13 shows the results of observing a pattern irradiated with an exposure dose of 100 mJ / cm2 in Example 9 using a CD-SEM. [Figure 17] 13 shows the results of observing a pattern irradiated with an exposure dose of 90 mJ / cm2 in Example 9 using a CD-SEM. [Figure 18] 13 shows the results of observing a pattern irradiated with an exposure dose of 80 mJ / cm2 in Example 9 using a CD-SEM. [Figure 19] 13 shows the results of observing a pattern irradiated with an exposure dose of 70 mJ / cm2 in Example 9 using a CD-SEM. [Figure 20] 13 shows the results of observing a pattern irradiated with an exposure dose of 60 mJ / cm2 in Example 9 using a CD-SEM. [Figure 21]13 shows the results of observing a pattern irradiated with an exposure dose of 50 mJ / cm2 in Example 9 using a CD-SEM. [Figure 22] 13 shows the results of observing a pattern irradiated with an exposure dose of 40 mJ / cm2 in Example 9 using a CD-SEM. [Figure 23] 13 shows the results of observing the pattern of an exposure dose of 500 μC / cm 2 in Example 10 using FE-SEM and an atomic force microscope (AFM). [Figure 24] 1 shows the results of measuring the remaining thickness of the photoresist pattern obtained in Experimental Example 2 using an AFM according to the amount of exposure. [Diagram 25] 1 shows the results of measuring the remaining thickness of the photoresist pattern obtained in Experimental Example 2 using an AFM according to the amount of exposure. [Figure 26] 1 shows the results of measuring the remaining thickness of the photoresist pattern obtained in Experimental Example 2 using an AFM according to the amount of exposure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0029] Unless otherwise defined herein, all technical and scientific terms have the same meaning as commonly understood by those skilled in the art to which the present invention belongs. The terms used in the description herein are merely for the purpose of effectively describing specific embodiments and are not intended to limit the present invention.

[0030] Also, as used in the specification and the appended claims, the singular forms "a," "an," and "the" can be intended to include the plural forms as well, unless the context clearly indicates otherwise.

[0031] In addition, the numerical ranges used in this specification include the lower limit and the upper limit, and all values ​​within the range, increments that are logically derived from the form and width of the range defined, and all values ​​limited therein, and all possible combinations of the upper and lower limits of the numerical ranges limited in different forms from each other. In the specification of the present invention, unless otherwise specified, values ​​outside the numerical range that may occur due to experimental error or rounding of values ​​are also included in the defined numerical range.

[0032] Furthermore, throughout this specification, "comprising," "including," "containing," or "having" an element means that it may further include other elements, but not that it excludes other elements, materials, or steps not further recited, unless specifically stated to the contrary.

[0033] In this specification, "room temperature" may mean a temperature in a state where the temperature is not artificially regulated, and may be, for example, 20°C to 40°C, or 20°C to 30°C, or 23°C to 26°C, or 21°C to 23°C.

[0034] The term "alkyl" as used herein means a saturated straight or branched chain acyclic hydrocarbon having 1 to 10 carbon atoms, preferably 1 to 5 carbon atoms. Representative saturated straight chain alkyls include -methyl, -ethyl, -n-propyl, -n-butyl, -n-pentyl, -n-hexyl, -n-heptyl, -n-octyl, -n-nonyl, and -n-decyl, while saturated branched alkyls include -isopropyl, -sec-butyl, -isobutyl, -tert-butyl, isopentyl, 2-methylhexyl, 3-methylbutyl, 2-methylpentyl, 3-methylpentyl, 4-methylpentyl, 2-methylhexyl, 3-methylhexyl, and the like.

[0035] The term "alkenyl" as used herein means a group derived from a straight or branched chain hydrocarbon containing one or more double bonds.

[0036] In the present specification, when described as "C1-C10", this means that the number of carbon atoms is 1 to 10. For example, C1-C10 alkyl means alkyl having 1 to 10 carbon atoms.

[0037] As used herein, the terms "halogen" and "halo" mean fluorine, chlorine, bromine, or iodine.

[0038] The term "haloalkyl" as used herein refers to an alkyl group in which one or more hydrogen atoms are replaced by halogen atoms. For example, haloalkyl includes -CF3, -CHF2, -CH2F, -CBr3, -CHBr2, -CH2Br, -CH2CI, -CHI2, -CH2I, -CH2-CF3, -CH2-CHF2, -CH2-CH2F, -CH2-CBr3, -CH2-CHBr2, -CH2-CH2Br, etc., where alkyl and halogen are as defined above.

[0039] The term "aryl" as used herein means a carbocyclic aromatic group containing from 5 to 10 ring atoms. Representative examples include, but are not limited to, phenyl, tolyl, xylyl, naphthyl, tetrahydronaphthyl, anthracenyl, fluorenyl, indenyl, azulenyl, and the like. Carbocyclic aromatic groups can be optionally substituted.

[0040] The term "cycloalkyl" as used herein means a monocyclic or polycyclic saturated ring having carbon and hydrogen atoms and no carbon-carbon multiple bonds. Examples of cycloalkyl groups include, but are not limited to, (C3-C10)cycloalkyl (e.g., cyclopropyl, cyclobutyl, cyclopentyl, cyclohexyl, and cycloheptyl). Cycloalkyl groups may be optionally substituted. In one embodiment, the cycloalkyl group is a monocyclic or bicyclic ring.

[0041] As used herein, the terms "carboxylic acid", "carboxyl" and "carboxy" refer to --COOH.

[0042] The term "alkyl carboxylate" as used herein means (alkyl)-COOH, where carboxylic acid is as defined above.

[0043] The term "alkylcarbonyl" as used herein means -CO-(alkyl), where alkyl is as defined above.

[0044] The term "alkylcarbonyloxy" as used herein means a (alkyl)-CO-O-* radical, where "alkylcarbonyl" is as defined above.

[0045] The present disclosure will now be described in detail, but by way of example only, and is not intended to be limited to the specific embodiments illustratively described.

[0046] The present disclosure provides tin compounds that include a central skeleton that includes a tin-oxygen double bond and an organic ligand bonded to the central skeleton.

[0047] The tin compound of the present disclosure can be thermodynamically stabilized by a double bond between a tin atom and an oxygen atom and an organic ligand bonded to the tin atom. This suppresses the formation of a dimer and allows the compound to exist in a monomolecular form, and when used as a photoresist material, the compound can have excellent photosensitivity and corrosion resistance. In addition, a photoresist pattern having excellent resolution, edge roughness, and mechanical strength can be formed by using a photoresist composition containing the compound.

[0048] The central skeleton may be tin dioxide (O=Sn=O) or tin monoxide (O=Sn). Tin compounds that have been mainly used as conventional photoresist materials have a Sn-C or Sn-N central skeleton, and when a tin atom dissociates from a carbon or nitrogen atom during exposure, a radical (-Sn·) with an unpaired electron on the tin atom is formed. This radical reacts with moisture and carbon dioxide in the surrounding environment during the photoresist pattern formation process to form -Sn-OH (hydroxyl group) or -Sn-O3CH (carbonate), which then undergo a condensation reaction to form Sn-O-Sn bridges or Sn-(CO3)-Sn bridges. In fact, it is difficult to control the concentrations of moisture and carbon dioxide at a constant level during the semiconductor manufacturing process, which leads to a problem of reduced reproducibility of the photoresist pattern.

[0049] However, in the tin compound according to the present disclosure, upon exposure, the organic ligand dissociates to generate thermodynamically unstable tin dioxide (O=Sn=O) or tin monoxide (O=Sn) molecules, and the molecules can exist within close distance due to the volume occupied by the organic ligands. This ensures a cross-sectional area that allows the addition reaction to occur with only a small amount of thermal energy supplied during exposure.

[0050] In one embodiment, the organic ligand can be a neutral ligand or an anionic ligand, but is not necessarily limited thereto as long as it achieves the objectives of the present disclosure.

[0051] As an example, the neutral ligand may be pyrazole, imidazole, dimethyl sulfide, or the like. sulfide, benzaldehyde, dimethyl sulfoxide (DMSO), pyrrolidine, n-butylamine, aniline, ethylbenzoate, pyrazine, n-propylamine, formamide, benzonitrile, pyrimidine, ethylenediamine, acetamide, methylformamide, t-butylamine, pyridine, propionitrile, triethylamine, ethylamine, diethylamine, pivalic acid, 2-pyrrolidone, water, diglyme, tetrahydrofuran (THF), nitric acid acid, benzylalcohol, t-butanol, ethyl benzene, benzoic acid, n-methylpyrrolidone, acetonitrile, furan, diethylformamide, n-propanol, 2-propanol, ethanol, methanol, trifluoroacetic acid, formic acid, dimethylformamide (DMF), 1,4-dioxane (1,The alkoxy group may be at least one selected from the group consisting of 4-dioxane, dimethylacetamide, benzoic acid, acetic acid, 1-butanol, ethyl acetate, dimethoxyethane, ethylene glycol, methoxy ethanol, phenol, and diethyl ether.

[0052] In one example, the anionic ligand is SiO4 4- , pyrazolate - , MeS - , Me2dtc - , N(EtOH)(EtO)2 2- , PhCH2S - , EtOCS 2- , thioacetate - , N(EtOH)2(EtO) - , salicylate 2- , CyS - , i-Pr2dtc - , O-Et-O 2- , MeOCS2 - , SiCl3 - , Py(COO-)3 3- , CH2S2 2- , Et2NCOO - , i-Pr2NCOO - , Si(PhCOO)4 4- , OCS2 2- , H2-citrate - , H-citrate 2- , C.N. - , EtS - , AsO4 3- , AsO3 3- , i-PrO - , Et2dtc - , i-PrS -, pyrrolidine-dtc - , O2 - , PhS. - , o-PhO2 2- , CF3CF2COO - , o-Ph(CH2COO)2 2- , m-Ph(CH2COO)2 2- , citrate 3- , N 3- , PO4 3- , OCN - , t-BuS - , Et-COO - , malate - , n-PrO - , i-PrOCS 2- , NO 2- , glycinate - , SO3 2- , PhCOO - , t-Bu-COO-(pivalate) - , HAsO4 2- , PhO - , SeO3 2- , SCN - , N(CH2COO)3 3- , PhCH2O - , MeOCOO - , MeO - , Ph(COOH)(COO)2 2- , i-Pr-COO - , furandicarboxylate - , N.C.-N.-C.N. - , EtO - , HCl2C-COO - , HO-Et-O - , m-Ph(COO)2 2- , HPO4 2- , SeCN - , pyrrolate - , H2PO2 2- , p-Ph(CH2COO)2 2- , imidazolate - , S 2- , H.C.O.O. -, Ph(COO)3 3- , o-Ph(COO)2 2- , n-BuO - , CH3COO - , O.H. - , Se 2- , t-BuO - , p-Ph(COO)2 2- , N(EtO)3 3- , MeO-Et-O - , C2O4 2- , Te 2- , Cl3CCOO - , MeSiO - , H.O.-Ph.-COO - , CF3CF2CF2COO - , GeCl3 - , Cl - , OTeF5 - , EDTA 4- , n-PrCOO - , CO3 2- , Et(COO)2 2- , S2O3 2- , AlMe4 - , BH3CN - , Et(COOH)(COO - ), Br - , I - , fumarate 2- , (O2N)2PhCOO - , CF3COO - , BH4 - , salicylate - , SnCl3 - , Ph(COOH)2(COO) - , (MeO)2PO2 - , S.H. - , -OOC-C≡C-COO - , Me2NCOO - , H2PO4 - , lactate - , p-O2NPhO - , saccharinate - , tartrate 2- , C(CN)3 - , SeO4 2-, CH3SO3 - , HCO3 - , SO4 2- , m-Ph(COOH)(COO) - , o-Ph(COOH)(COO) - , p-H2N - Ph-SO3 - , Naph(SO3)2 2- , C2O4H - , ClO3 - , H.C.B. 11 H 11 - , F - , NO3 - , PhSO3 - , B(PhO2)2 - , ReO4 - , SiF6 2- , p - Ph(COOH)(COO) - , p-Me-PhSO3 - (OTs), B 10 H 10 2- , BHEt3 - , B(CN)4 - , Picrate, B 12 H 12 2- , H.C.B. 11 H 11 - x Cl x - , H-tartrate - , AlCl4 - , CF3SO3 - (triflate), HSO4 - , (F3C)3C-O - , triflimidate - , GaCl4 - , SbCl6 - , ClO4 - , S2O6 2- , AsF6 - , SbF6 - , BF4 - , I3 - , BH(C6F5)3 - , B(3,5-PhCl2)4- , Al(OC(CF3)3)4 - , BMe(C6F5)3 - , PF6 - , BPh4 - , B(C6F5)4 - and BArF4 - The number of the at least one selected from the group consisting of:

[0053] In one embodiment, the organic ligand may be at least one selected from the group consisting of formic acid, C1-C10 alkyl carboxylate, C2-C10 alkenyl carboxylate, C3-C10 cycloalkyl carboxylate, C6-C20 aryl carboxylate, halo C1-C10 alkyl carboxylate, C1-C10 alkylcarbonyloxy, C2-C10 alkenylcarbonyloxy, C3-C10 cycloalkylcarbonyloxy, C6-C20 arylcarbonyloxy, halo C1-C10 alkylcarbonyloxy, C1-C10 alkylcarbonylamine, and halo C1-C10 alkylcarbonylamine, which is preferred in that the ligand dissociation reaction is more effectively carried out upon exposure.

[0054] In a preferred embodiment, the organic ligand may be any one or more selected from the group consisting of formic acid, C1-C10 alkyl carboxylate, halo C1-C10 alkyl carboxylate, and halo C1-C10 alkylcarbonyloxy. Specifically, the organic ligand may be any one or more selected from the group consisting of C1-C5 alkyl carboxylate, halo C1-C5 alkyl carboxylate, and halo C1-C5 alkylcarbonyloxy. When the organic ligand is included, the tin compound can be thermodynamically more stable by bonding an oxygen atom present in the organic ligand with a tin atom.

[0055] For example, the tin compound may be represented by the following formulas 1 to 4.

[0056] [Chemical formula 1] JPEG2025051654000006.jpg37170

[0057] [Chemical formula 2] JPEG2025051654000007.jpg37170

[0058] [Chemical formula 3] JPEG2025051654000008.jpg23170

[0059] [Chemical formula 4] JPEG2025051654000009.jpg14170

[0060] (In the above Chemical Formulas 1 to 4, R1 to R7 are each independently hydrogen, C1-C10 alkyl, or haloC1-C10 alkyl.

[0061] For example, R1 to R7 may be, independently of each other, hydrogen, C1-C5 alkyl, or haloC1-C5 alkyl.

[0062] For example, R1 to R4 may be each independently C1-C5 alkyl or haloC1-C5 alkyl, and R5 to R7 may be each independently hydrogen, C1-C5 alkyl or haloC1-C5 alkyl.

[0063] For example, R1 and R2 may be the same as each other and are C1-C5 alkyl or haloC1-C5 alkyl, R3 and R4 may be the same as each other and are C1-C5 alkyl or haloC1-C5 alkyl, and R5 to R7 may be each independently hydrogen, C1-C5 alkyl, or haloC1-C5 alkyl.

[0064] For example, R1 and R2 may be the same as each other and be C1-C3 alkyl or haloC1-C3 alkyl, R3 and R4 may be the same as each other and be C1-C3 alkyl or haloC1-C3 alkyl, and R5 to R7 may be each independently be hydrogen, C1-C3 alkyl, or haloC1-C3 alkyl.

[0065] The present disclosure also provides a photoresist composition comprising the above-described tin compound.

[0066] A photoresist composition according to one embodiment is an inorganic resist for extreme ultraviolet (EUV) and / or electron beam lithography, in which chemical contrast is expressed by an additive reaction between inorganic components upon irradiation with extreme ultraviolet (EUV) or an electron beam, and a pattern can be formed in an optional development step.

[0067] The tin compound according to the present disclosure has a structure in which a central skeleton containing a tin-oxygen double bond is bonded to an oxygen atom of an organic ligand, and the organic ligand dissociates upon exposure to light, and the molecules exist within close distance due to the volume occupied by the organic ligand, and can be polymerized with each other by an addition reaction.

[0068] The photoresist composition according to one embodiment may be an extreme ultraviolet (EUV) photoresist composition.

[0069] Since the photoresist composition according to an embodiment has excellent extreme ultraviolet light sensitivity and corrosion resistance, a photoresist pattern using the composition can be formed with a thin thickness even in an ultra-fine pattern, and a high-quality photoresist pattern with excellent resolution and sensitivity can be formed.

[0070] In one embodiment, the photoresist composition according to the present disclosure may include a tin compound and a solvent. Any type of solvent may be used as long as the tin compound according to one embodiment is soluble in the solvent. For example, the solvent may be one or more selected from the group consisting of water, methanol, acetic acid, chlorobenzene, chloroform, ethyl lactate, and tetrahydrofuran.

[0071] In one embodiment, the photoresist composition may contain 0.1 to 50 parts by weight of the above-mentioned tin compound, based on 100 parts by weight of the total weight of the photoresist composition. Specifically, the tin compound may be contained in an amount of 0.1 to 30 parts by weight, more specifically, 0.5 to 10 parts by weight, and even more specifically, 1 to 5 parts by weight, based on 100 parts by weight of the photoresist composition. When the content of the tin compound satisfies the above range, a photoresist pattern having better resolution and sensitivity can be formed, which is preferable.

[0072] The present disclosure also provides a method for forming a photoresist pattern, comprising the step of dissociating an organic ligand of an organometallic compound upon exposure to light and carrying out an addition reaction between metal molecules.

[0073] According to an embodiment of the method for forming a photoresist pattern, the conventional problem of reduced reproducibility of a pattern due to external environments such as moisture and carbon dioxide can be prevented, and a high-quality photoresist pattern can be formed without a step of reacting with gas molecules during the process, which is very useful industrially.

[0074] As an example, the organometallic compound may contain a metal having excellent photosensitivity as a central metal, specifically, may be an organotin compound. Examples of applicable organic ligands are as described above.

[0075] The method for forming a photoresist pattern according to the present disclosure includes a step of performing an additive reaction between metal molecules during exposure, thereby preventing the conventional problem of reduced pattern reproducibility due to external environments such as moisture and carbon dioxide, etc. In other words, a high-quality photoresist pattern having excellent reproducibility and process stability can be formed in a large-area process.

[0076] The present disclosure also provides a method for forming a photoresist pattern, comprising the steps of: (a) applying a photoresist composition containing the organometallic compound as described above to a substrate to form a thin film; (b) exposing the thin film to light; and (c) developing the exposed thin film with a developer solution.

[0077] In one embodiment, the organometallic compound may include a central skeleton containing a tin-oxygen double bond and organic ligands bonded to the central skeleton.

[0078] As an example, the central skeleton may be tin dioxide (O=Sn=O) or tin monoxide (O=Sn). According to the method for forming a photoresist pattern according to the present disclosure, upon exposure, the organic ligands of the organometallic compound are dissociated, and due to the volume occupied by the organic ligands, the central skeleton molecules are within a close distance from each other and can be polymerized with each other by an addition reaction. Schematic diagrams of this mechanism are shown in FIG. 1 and FIG. 2.

[0079] In the method for forming a photoresist pattern according to one embodiment, the photoresist composition in step (a) may be applied to a substrate by any method known in the art, including, but not limited to, spin coating, dipping, roller coating, bar coating, spray coating, inkjet printing, and screen printing.

[0080] For example, the photoresist composition may be applied onto a substrate by a spin coating method, and the thickness of the photoresist film may be adjusted based on the speed of a spinner and the time for which coating is performed. For example, spin coating may be performed at a speed of 100 rpm to 5000 rpm, specifically 2000 rpm to 4000 rpm, for 1 second to 60 seconds, specifically 20 seconds to 40 seconds, but is not limited thereto.

[0081] In one embodiment, the step (b) is a step of exposing the thin film formed in the step (a), and the exposure may be performed by any one selected from an electron beam (E-beam), extreme ultraviolet (EUV), I-line, a krypton fluoride (KrF) laser, an argon fluoride (ArF) laser, deep ultraviolet (DUV), vacuum ultraviolet (VUV), X-ray, and an ion beam, and is preferably, but not necessarily limited to, extreme ultraviolet or an electron beam.

[0082] In one embodiment, the method may further include a step of heating the thin film formed in step (a) after step (a) and before step (b). The step of heating the thin film is a PAB (Postapply Bake) process, which may be performed at 50 to 300° C., specifically, at a temperature of 100 to 200° C. or 110 to 180° C. for 0.5 to 10 minutes or 0.5 to 5 minutes, thereby removing the solvent contained in the photoresist composition and improving the adhesive strength between the thin film and the substrate.

[0083] In one embodiment, the thickness of the photoresist thin film formed on the substrate may be 1 to 100 nm, or 5 to 50 nm, specifically 5 to 30 nm, where the thickness of the thin film may be measured after applying the photoresist composition to the substrate and then carrying out the above-mentioned PAB process.

[0084] The substrate on which the photoresist composition is applied may include one or more conductive layers selected from aluminum, copper, molybdenum, titanium, tungsten, alloys of these metals, nitrides of these metals, or silicides of these metals, one or more dielectric layers selected from silicon oxide, silicon nitride, silicon oxynitride, and metal oxide, a semiconductor layer such as single crystal silicon, and combinations thereof, located on a lower base substrate. Here, the lower base substrate may be in the form of a wafer or film, and may be a laminate in which semiconductors, ceramics, metals, polymers, or two or more materials selected from these are laminated in layers.

[0085] For example, the lower base substrate may be a semiconductor substrate, and non-limiting examples of the semiconductor substrate may include a group IV semiconductor including silicon (Si), germanium (Ge) or silicon germanium (SiGe), a group III-V semiconductor including gallium arsenide (GaAs), indium indium (InP) or gallium indium (GaP), a group II-VI semiconductor including cadmium sulfide (CdS) or zinc telluride (ZnTe), a group IV-VI semiconductor including lead sulfide (PbS), or a laminate in which two or more materials selected from the above are laminated in layers. Here, the semiconductor substrate may be in the form of a wafer or film, and may be a semiconductor, a ceramic, a metal, a polymer, or a laminate in which two or more materials selected from the above are laminated in layers.

[0086] In one embodiment, the method may further include a step of heating the exposed thin film after the step (b). Specifically, the step of heating the exposed thin film is a PEB (postexposure bake) process, which may be performed at 50 to 300° C., specifically, at a temperature of 100 to 200° C. or 100 to 150° C. for 1 to 15 minutes or 1 to 5 minutes. This can further increase the difference in solubility in the developer between the exposed region and the unexposed region.

[0087] In one embodiment, before and / or after the step (b), a UVbake process step of baking the photoresist thin film by ultraviolet (UV) irradiation may be further included, which can improve the quality of the inorganic resist pattern such as DtS (dose-to-size), edge roughness (LER), line width (half-pitch, HP), etc. As an example, the UVbake process may use a UV lamp, an i-line light source, a KrF, an ArF laser light source, etc., but is not necessarily limited thereto.

[0088] In one embodiment, after the step (c), a hard bake step of baking the photoresist thin film may be further included, and the hard bake step may further improve the quality of the inorganic resist pattern, such as DtS (dose-to-size), edge roughness (LER), line width (half-pitch, HP), etc. As an example, the hard bake step may be performed at a temperature of 100°C to 200°C, specifically 110°C to 180°C, for 0.5 minutes to 10 minutes, specifically 0.5 minutes to 5 minutes, but is not necessarily limited thereto, and the process conditions may be appropriately changed depending on the solvent used.

[0089] The light source may be a KrF or ArF laser light source, but is not limited to this.

[0090] In one embodiment, the photoresist pattern may be a positive type that becomes soluble in a developer by exposure to light used in the exposure step, or a negative type that becomes insoluble in a developer, specifically, a negative type. That is, depending on the solubility of the thin film in the developer, the pattern formed by the method for forming a photoresist pattern may be a positive type or a negative type pattern, specifically, a negative type pattern.

[0091] In one embodiment, the step (c) is a step of developing the exposed thin film using a developer solution, and specifically, the developer solution may be any type of substance known in the art, and may include, for example, a C2-10 alkene or a quaternary ammonium salt. A specific example of the C2-10 alkene may be hexene. A specific example of the quaternary ammonium salt may be tetramethylammonium hydroxide (TMAH), tetrabutylammonium hydroxide (TBAH), tetrapropylammonium hydroxide (TPAH), tetraethylammonium hydroxide (TEAH), or a mixture thereof. For example, the developer may include, but is not limited to, 1 to 30% by weight, specifically, 1 to 5% by weight of a quaternary ammonium salt.

[0092] The present invention also provides a semiconductor device including a photoresist pattern formed by the above-mentioned method for forming a photoresist pattern. The semiconductor device includes a photoresist pattern formed with excellent resolution and sensitivity by the above-mentioned method, thereby realizing a higher quality semiconductor device.

[0093] Examples and experimental examples are specifically illustrated below. However, the examples and experimental examples described below are only a partial example, and the technology described in this specification is not limited thereto.

[0094] [Example 1] Preparation of tin compound 1 JPEG2025051654000010.jpg37170

[0095] 0.304g of tin oxide powder (purchased from QURES Co., Ltd.) was placed in a round-bottom flask, followed by 16ml of methanol and 24ml of acetic acid. After stirring at room temperature for 30 minutes, the mixture was heated and stirred at 70℃ for 15 hours. The solvent was then removed using a vacuum pump to obtain a yellow solid tin compound 1 (acetic acid-stabilized tin dioxide).

[0096] A MALDI-TOF mass spectrometer (MALDI-TOF MS) was used to analyze the structure of the obtained tin compound. Tin compound 1 was dissolved in methanol at 1 wt% to prepare a solution, which was then filtered through a 5 ml PTFE syringe filter and used for analysis. The analysis results are shown in Figure 3, and the molecular formula of the peak corresponding to (a) in Figure 3 was estimated by isotope distribution simulation calculation in Figure 4, and the result corresponding to (b) is shown in Figure 5. Referring to Figure 4, [SnO2(CH3COOH)2+H] was found with a distributed mass of around 272.929 Da. + When the molecular formula was substituted, the isotope distribution graph was confirmed to match. Also, referring to Figure 5, the isotope distribution graph shows that the isotope distribution graph is consistent with that of [SnO2(CH3COOH)2+Na] at a distributed mass of approximately 294.944 Da. + When the molecular formula was substituted, it was confirmed that the isotope distribution graph matched. The solid line shows the MALDI-TOF analysis results, and the dotted line shows the data obtained by simulation calculation.

[0097] In addition, the obtained tin compound was analyzed in a solid powder state by X-ray photoelectron spectroscopy (XPS), and the results are shown in Figure 6. Referring to Figure 6, a peak was observed at 486.7 eV for Sn3d3 and 495.1 eV for Sn3d5, confirming that the tin atom in the obtained tin compound 1 has a tetravalent oxidation number.

[0098] [Example 2] Preparation of tin compound 2 JPEG2025051654000011.jpg38170

[0099] The same procedure was carried out as in Example 1, except that 0.608 g of tin oxide powder was used, and the mixture was stirred at room temperature for 30 minutes, and then stirred while heating for 1 hour, to obtain tin compound 2 (acetic acid-stabilized tin monoxide).

[0100] To analyze the structure of the obtained tin compound, FD-MS (Field Desorption-Mass Spectrometry) analysis was performed. Tin compound 2 was dissolved in acetic acid at 2 wt% to prepare a solution, which was then filtered through a 5 ml PTFE syringe filter and used for analysis. The analysis results are shown in FIG. 7, and the molecular formula estimated by isotope distribution simulation calculation is shown in FIG. 8. Referring to FIG. 8, [SnOLi] was found with a distributed mass of around 142.91 Da. + When the molecular formula was substituted, it was confirmed that the isotope distribution graphs matched. Li is expected to be derived from the promoter LiI used in acetic acid synthesis. The black solid line is the FD-MS analysis result, and the red dotted line is the data obtained by simulation calculation.

[0101] The obtained tin compound was analyzed in a solid powder state by FT-IR spectroscopy, and the results are shown in Figure 9. -1 The peak confirmed the presence of C=O, and this confirmed that acetic acid was not completely removed from the obtained tin compound 2 and was still present.

[0102] [Example 3] Preparation of tin compounds 3-1 and 3-2 JPEG2025051654000012.jpg31170

[0103] The same procedure as in Example 2 was carried out except that trifluoroacetic acid was used instead of acetic acid, to obtain tin compounds 3-1 and 3-2.

[0104] To analyze the structure of the obtained tin compounds, a MolDietof mass spectrometer (MALDI-TOF MS) was used, and tin compounds 3-1 and 3-2 were dissolved in methanol at 1 wt% to prepare a solution, which was then filtered through a 5 ml PTFE syringe filter and used for analysis. The analysis result graph is shown in Figure 10, and the results of estimating the molecular formula of the peak corresponding to (a) in Figure 10 by isotope distribution simulation calculation are shown in Figure 11, and the results corresponding to (b) are shown in Figure 12.

[0105] Referring to FIG. 11, [SnO(CF3COOH)+Na] is distributed at a mass near 271.93 Da. + When the molecular formula was substituted, it was confirmed that the isotope distribution graph matched, and it was confirmed that a compound corresponding to the tin compound 3-1 was produced.

[0106] 12, when the molecular formula SnO(CF3COO)(HCOO) was substituted with the distributed mass near 293.98 Da, the isotope distribution graph was confirmed to match, and it was confirmed that a compound corresponding to the tin compound 3-2 was produced. The solid line is the MALDI-TOF analysis result, and the dotted line is the data obtained by simulation calculation.

[0107] [Examples 4 to 8] Preparation of photoresist composition The tin compounds obtained in Examples 1 to 3 were dissolved in a solvent to prepare photoresist compositions. The content of the tin compounds and the type of the solvent are shown in Table 1 below.

[0108] [Table 1]

[0109] [Example 9] Formation of photoresist pattern using extreme ultraviolet (EUV) A p-Si silicon wafer on which a 100 nm thick thermal oxide film (SiO2) was deposited was cut into a size of 1.5 cm x 1.5 cm and then cleaned by sonication in acetone for 20 minutes. The photoresist composition prepared in Example 4 was applied to the wafer and spin-coated (1500 rpm, 30 s) to prepare a thin film, which was then heated at 90°C for 1 minute to remove the solvent. Extreme ultraviolet (EUV) was applied to the prepared thin film at 30 to 130 mJ / cm. 2 The exposed film was then heated at 90°C for 1 minute for PEB, immersed in a 2.38 wt% tetramethylammonium hydroxide (TMAH) developer, and developed for 10 seconds to obtain a pattern. The results were observed using a CD-SEM (Critical Dimension Scanning Electron Microscope) and were irradiated with an exposure dose of 130 mJ / cm. 2 The pattern irradiated with an exposure dose of 120 mJ / cm is shown in Figure 13. 2 The pattern irradiated with an exposure dose of 110 mJ / cm is shown in Figure 14. 2 The pattern irradiated with an exposure dose of 100 mJ / cm is shown in Figure 15. 2 The pattern irradiated with an exposure dose of 90 mJ / cm is shown in Figure 16. 2 The pattern irradiated with an exposure dose of 80 mJ / cm is shown in Figure 17. 2 The pattern irradiated with an exposure dose of 70 mJ / cm is shown in Figure 18. 2 The pattern irradiated with an exposure dose of 60 mJ / cm is shown in Figure 19. 2 The pattern irradiated with an exposure dose of 50 mJ / cm is shown in Figure 20. 2 The pattern irradiated with an exposure dose of 40 mJ / cm is shown in Figure 21. 2 The pattern irradiated with an exposure dose of is shown in Figure 22. This confirmed that the photoresist composition containing the tin compound according to the present disclosure can stably form a high-quality ultrafine pattern even with a low exposure dose.

[0110] [Example 10] Formation of photoresist pattern using electron beam A p-Si silicon wafer on which a 100 nm thick thermal oxide film (SiO2) was deposited was cut into a size of 1.5 cm x 1.5 cm and then cleaned by sonication in acetone for 20 minutes. The photoresist composition prepared in Example 5 was applied to the wafer and spin-coated (3000 rpm, 30 s) to prepare a thin film, which was then heated at 50°C for 1 minute to remove the solvent. The thin film was then subjected to irradiation with an electron beam at 200-5000 μC / cm 2 The sample was exposed to an exposure dose of 500 μC / cm. The sample was then immersed in a 2.38 wt% developer of tetramethylammonium hydroxide (TMAH) for 10 seconds to obtain a pattern. The results were observed with an atomic force microscope (AFM) and a field emission scanning electron microscope (FE-SEM), and are shown in FIG. 23. After development with an atomic force microscope (AFM), the remaining thickness of the exposed and non-exposed areas was analyzed, and a 500 μC / cm 2 It was confirmed that ultrafine patterns were stably formed at this exposure dose.

[0111] [Experimental Example 1] Measurement of ND (Non-dissolution) temperature A p-Si silicon wafer on which a thermal oxide film (SiO2) of 100 nm thickness was deposited was cut into a size of 1.5 cm x 1.5 cm, and then sonicated in acetone for 20 minutes to clean it. The photoresist compositions prepared in Examples 4 to 8 were applied to the wafer, spin-coated (1500 to 3000 rpm, 30 s) to prepare a thin film, and then it was observed whether it was dissolved in a developer while changing the temperature. A 2.38 wt% solution of tetramethylammonium hydroxide (TMAH) was used as the developer, and the temperature at which it was no longer dissolved in the developer when heated was defined as the ND (Nondissolution) temperature. The analysis results are shown in Table 2 below. This confirmed the maximum temperature applicable to the PAB and PEB processes of the photoresist composition according to the present disclosure, and it was found that the photoresist composition according to the present disclosure has excellent thermal stability, does not collapse the pattern even at high temperatures, and can form a high-quality photoresist pattern.

[0112] [Table 2]

[0113] [Experimental Example 2] Measurement of electron beam sensitivity The photoresist compositions prepared in Examples 5 to 7 were used to measure the electron beam sensitivity.

[0114] A p-Si silicon wafer on which a thermal oxide film (SiO2) of 100 nm thickness was deposited was cut into a size of 1.5 cm x 1.5 cm, and then cleaned by sonication in acetone for 20 minutes. The photoresist compositions prepared in Examples 5 to 7 were applied to the wafer and spin-coated (3000 rpm, 30 s) to prepare a thin film, and a PAB process was carried out. The prepared thin film was irradiated with an electron beam at 1 to 1000 μC / cm 2 The exposed film was then irradiated with an exposure dose of 100 nm. The film was then immersed in a 2.38 wt % developer of tetramethylammonium hydroxide (TMAH) and developed for 10 seconds to obtain a pattern. The composition and process conditions used are shown in Table 3 below. The thickness of the obtained pattern was measured using an atomic force microscope (AFM), and the results are shown in Figures 24 to 26. 50 means the exposure dose when the remaining thickness of the thin film is half, and D 100 means the exposure dose at which the remaining thickness of the thin film is at its maximum. The thickness of the thin film was calculated as the average thickness of the thin film remaining after exposure at the exposure dose.

[0115] [Table 3]

[0116] 24 is a graph showing the thickness of the thin film remaining after development of the pattern obtained using the photoresist composition of Example 5. The measured value was D04.5 μC / cm 2 , D 50 6.0μC / cm 2 , D 100 8.25μC / cm 2 The contrast γ, which is the gradient of the graph of the film thickness according to the exposure dose, was found to be 3.79.

[0117] FIG. 25 is a graph showing the thickness of the thin film remaining after development of the pattern obtained using the photoresist composition of Example 6. The measured values ​​are D 50 22.88μC / cm 2 The contrast γ, which is the gradient of the graph of the film thickness according to the exposure dose, was found to be 2.30.

[0118] 26 is a graph showing the thickness of the thin film remaining after development of the pattern obtained using the photoresist composition of Example 7. The measured value was D082.64 μC / cm 2 , D 50 100μC / cm 2 , D 100 121μC / cm 2 The contrast γ, which is the gradient of the graph of the film thickness according to the exposure dose, was found to be 6.04.

[0119] As can be seen from the above, the photoresist composition including the tin compound according to one embodiment of the present disclosure can simultaneously realize excellent photosensitivity and corrosion resistance, and can be used to manufacture high-quality semiconductor devices. In addition, the organic ligand of the tin compound dissociates during exposure, and is polymerized with each other through an addition reaction between tin molecules, thereby generating a pattern in the development process, thereby preventing the conventional problem of reduced reproducibility of patterns due to external environments such as moisture and carbon dioxide.

[0120] As described above, in this specification, the present disclosure has been described using specific details and limited examples, but these are provided to facilitate a more general understanding of the present disclosure. The present disclosure is not limited to the above-mentioned examples, and various modifications and variations can be made from such descriptions by a person having ordinary knowledge in the field to which the present disclosure pertains.

Claims

1. A central skeleton containing a tin-oxygen double bond; and an organic ligand attached to the central skeleton.

2. The tin compound according to claim 1 , wherein the central skeleton is tin dioxide (O═Sn═O) or tin monoxide (O═Sn).

3. The tin compound according to claim 1, wherein the organic ligand is at least one selected from the group consisting of formic acid, C1-C10 alkyl carboxylate, C2-C10 alkenyl carboxylate, C3-C10 cycloalkyl carboxylate, C6-C20 aryl carboxylate, halo C1-C10 alkyl carboxylate, C1-C10 alkylcarbonyloxy, C2-C10 alkenylcarbonyloxy, C3-C10 cycloalkylcarbonyloxy, C6-C20 arylcarbonyloxy, halo C1-C10 alkylcarbonyloxy, C1-C10 alkylcarbonylamine, and halo C1-C10 alkylcarbonylamine.

4. The tin compound according to claim 1, wherein the tin compound is represented by the following chemical formulas 1 to 4: [Chemical formula 1] [Chemical formula 2] [Chemical formula 3] [Chemical formula 4] In the above chemical formulas 1 to 4, R 1 ~R 7 are each independently hydrogen, C1-C10 alkyl, or haloC1-C10 alkyl.

5. R 1 ~R 4 are, independently of each other, C1-C5 alkyl or haloC1-C5 alkyl; R 5 ~R 7 are each independently hydrogen, C1-C5 alkyl or haloC1-C5 alkyl.

6. A photoresist composition comprising the tin compound according to any one of claims 1 to 5.

7. The photoresist composition according to claim 6, wherein the photoresist composition is an inorganic resist for extreme ultraviolet (EUV) and / or electron beam lithography, and when irradiated with extreme ultraviolet (EUV) or an electron beam, chemical contrast is expressed by an additive reaction between inorganic components, and a pattern is formed in an optional development process.

8. 7. The photoresist composition of claim 6, wherein the photoresist is an extreme ultraviolet (EUV) photoresist.

9. 7. The photoresist composition according to claim 6, wherein the total content of the tin compounds is 0.1 to 50 parts by weight based on 100 parts by weight of the photoresist composition.

10. 7. The photoresist composition according to claim 6, wherein the total content of the tin compounds is 0.1 to 10 parts by weight based on 100 parts by weight of the photoresist composition.

11. A method for forming a photoresist pattern, comprising the step of: upon exposure, dissociating an organic ligand of an organometallic compound and carrying out an addition reaction between metal molecules.

12. (a) applying a photoresist composition containing the organometallic compound to a substrate to form a thin film; (b) exposing the thin film to light; 12. The method for forming a photoresist pattern according to claim 11, further comprising: (c) developing the exposed thin film with a developer solution.

13. 12. The method of forming a photoresist pattern according to claim 11, wherein the organometallic compound comprises a central skeleton containing a tin-oxygen double bond, and an organic ligand bonded to the central skeleton.

14. 14. The method of claim 13, wherein the central skeleton is tin dioxide (O=Sn=O) or tin monoxide (O=Sn).

15. 13. The method of claim 12, wherein the exposure in step (b) is performed by any one selected from the group consisting of an electron beam (E-beam), extreme ultraviolet (EUV), I-line, a krypton fluoride (KrF) laser, an argon fluoride (ArF) laser, deep ultraviolet (DUV), vacuum ultraviolet (VUV), X-ray, and an ion beam.

16. 13. The method for forming a photoresist pattern according to claim 12, further comprising the step of heating the thin film formed in the step (a) before the step (b).

17. 13. The method for forming a photoresist pattern according to claim 12, further comprising the step of heating the exposed thin film after the step (b).

18. A semiconductor device comprising a photoresist pattern formed by the method for forming a photoresist pattern according to any one of claims 11 to 17.

Citation Information

Patent Citations

  • Metal oxide dispersion

    JP2010092782A

  • Method for producing liquid tin(ii) alkoxide

    JP2016505531A

  • Organometallic cluster photoresists for EUV lithography

    US20210087210A1

  • Cyclosiloxane-based cluster compound and photoresist composition comprising the same

    KR1020240103989A

  • Cyclo siloxane-based compound incorporated with carbonyl group and sulfonyl group, preparation method thereof and photoresist composition containing the same

    KR1020240104028A